2002
DOI: 10.1152/ajpheart.00474.2002
|View full text |Cite
|
Sign up to set email alerts
|

ACh and adenosine activate PI3-kinase in rabbit hearts through transactivation of receptor tyrosine kinases

Abstract: adenosine activate PI3-kinase in rabbit hearts through transactivation of receptor tyrosine kinases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
90
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(94 citation statements)
references
References 43 publications
4
90
0
Order By: Relevance
“…SFKs participate in GPCR-mediated transactivation of several RTKs (Keely et al, 2000;Lee and Chao, 2001;Krieg et al, 2002;Zahradka et al, 2004). Although intermediates in the pathway, we do not know whether SFKs directly phosphorylate these receptor tyrosine kinases or if the effect is indirect.…”
Section: Discussionmentioning
confidence: 97%
“…SFKs participate in GPCR-mediated transactivation of several RTKs (Keely et al, 2000;Lee and Chao, 2001;Krieg et al, 2002;Zahradka et al, 2004). Although intermediates in the pathway, we do not know whether SFKs directly phosphorylate these receptor tyrosine kinases or if the effect is indirect.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, transactivation of EGFR via G q -coupled receptors would decrease chloride secretion in T84 epithelial cells as a result of activation of MAPK (19). However, the coupling to either downstream effector may not be so straightforward as the occupancy of G q -coupled receptor (e.g., acetylcholine and adenosine A 1 receptor) in rabbit hearts leads to PI3-kinase activation through EGFR transactivation (20). Finally, the coupling of adenosine receptors to MAPK has been established (36), but its potential role in modulating chloride secretion remains to be examined.…”
Section: Discussionmentioning
confidence: 99%
“…In cardiac cells, EGFR transactivation has been linked to angiotensin (Rakesh et al, 2010), muscarinic (Krieg et al, 2002;Krieg et al, 2004;Miao et al, 2015), endothelin (Kodama et al, 2002;Chen et al, 2006), opioid (Cao et al, 2005;Cohen et al, 2007;Forster et al, 2007;Zhang et al, 2015), bradykinin (Methner et al, 2009), adrenergic (Noma et al, 2007;Grisanti et al, 2014), adenosine (Williams-Pritchard et al, 2011), and sphoingosine-1 phosphate (S1P) (Hofmann et al, 2009) GPCRs, with transactivation via angiotensin II (Ang II) perhaps the most well studied. Several Gq-linked receptors (Ang II, ET-1, -ARs) may promote cardiac hypertrophy/remodelling, whereas transactivation by adenosine, opioid, bradykinin or muscarinic receptors may be protective, enhancing cell survival.…”
Section: Mechanisms Of Egfr Transactivationmentioning
confidence: 99%
“…Krieg et al (2002) initially found that acetylcholine triggered myocardial EGFR and Akt phosphorylation in an AG1478 sensitive manner, although cardiac protection appeared insensitive to the inhibitor. However, their subsequent work showed antiinfarct effects of acetylcholine and the-opioid agonist DADLE were associated with EGFR phosphorylation, and blocked by metalloproteinase inhibition (Krieg et al, 2004).…”
Section: Role Of the Egfr In Gpcr-triggered Cardioprotectionmentioning
confidence: 99%